Faulkner and print culture - Watson, Jay; Harker, Jaime; Thomas, James G., Jr (Book collections on Project MUSE., 2017)
"With contributions by: Greg Barnhisel, John N. Duvall, Kristin Fujie, Sarah E. Gardner, Jaime Harker, Kristi Rowan Humphreys, Robert Jackson, Mary A. Knighton, Jennifer Nolan, Carl Rollyson, Tim A. Ryan, Jay Satterfield, Erin A. Smith, and Yung-Hsing Wu"--